2013
DOI: 10.1371/journal.pone.0068213
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Primary HIV Drug Resistance in a Subtype C Dominated Epidemic in Mozambique

Abstract: ObjectiveIn Mozambique, highly active antiretroviral treatment (HAART) was introduced in 2004 followed by decentralization and expansion, resulting in a more than 20-fold increase in coverage by 2009. Implementation of HIV drug resistance threshold surveys (HIVDR-TS) is crucial in order to monitor the emergence of transmitted viral resistance, and to produce evidence-based recommendations to support antiretroviral (ARV) policy in Mozambique.MethodsWorld Health Organization (WHO) methodology was used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…Between 2010 and 2017, EFV and 3TC were recommended for first line treatment in Portugal. This was also the most frequent NRTI and NNRTI-resistance mutation (M184V and K103N) among pre-treated patients and was previously reported among antiretroviral-naïve patients living in Portuguese Speaking countries [38,40,41]. A low prevalence of TDR to PIs within migrants reflects the scarce administration of this antiretroviral as first line in their countries of origin.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Between 2010 and 2017, EFV and 3TC were recommended for first line treatment in Portugal. This was also the most frequent NRTI and NNRTI-resistance mutation (M184V and K103N) among pre-treated patients and was previously reported among antiretroviral-naïve patients living in Portuguese Speaking countries [38,40,41]. A low prevalence of TDR to PIs within migrants reflects the scarce administration of this antiretroviral as first line in their countries of origin.…”
Section: Discussionsupporting
confidence: 62%
“…Among migrants from different Portuguese-speaking countries, migrants from Mozambique showed a high resistance rate of 17.4%, compared to the average of other Portuguese-speaking countries analyzed herein (7-10%). These results are discordant with other studies involving patients from Mozambique between the years 2007 and 2009 that showed a low prevalence of 5% of primary drug resistance based on WHO mutation list [37,38]. These differences may be related to four hypotheses: 1) The rate of TDR involving increased, since the studies conducted in this area are older.…”
Section: Discussioncontrasting
confidence: 46%
“…File was then converted to MEGA file format and using MEGA file format phylogenetic tree was built using MEGA 5.2 tool, using Maximum Parsimony approach [ 23 ]. Tool has been previous cited in other research articles [ 24 26 ] for constructing Phylogenetic tree. Given sequences were then uploaded in GLAM2 tool [ 27 ] of MEME suite [ 28 ] to identify motifs present in group of related protein sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Further, virological monitoring maybe an urgent need given that in the capital Maputo, a transmitted drug resistance rate of <5% was calculated from multiple surveys[18]. We were especially interested in further validating a pooled qualitative PCR assay in Mozambique that would allow for subsequent genotyping to assess for drug resistance in cases of virologic failure[12].…”
Section: Resultsmentioning
confidence: 99%